Intrinsic Sex‐Linked Variations in Osteogenic and Adipogenic Differentiation Potential of Bone Marrow Multipotent Stromal Cells. Issue 2 (February 2015) - Bragdon, Beth; Burns, Robert; Baker, Amelia H.; Belkina, Anna C.; Morgan, Elise F.; Denis, Gerald V.; Gerstenfeld, Louis C.; Schlezinger, Jennifer J.
<x xml:space="preserve">Abstract</x> Bone formation and aging are sexually dimorphic. Yet, definition of the intrinsic molecular differences between male and female multipotent mesenchymal stromal cells (MSCs) in bone is lacking. This study assessed sex‐linked differences in MSC differentiation in 3‐, 6‐, and 9‐month‐old C57BL/6J mice. Analysis of tibiae showed that female mice had lower bone volume fraction and higher adipocyte content in the bone marrow compared to age‐matched males. While both males and females lost bone mass in early aging, the rate of loss was higher in males. Similar expression of bone‐ and adipocyte‐related genes was seen in males and females at 3 and 9 months, while at 6 months, females exhibited a twofold greater expression of these genes. Under osteogenic culture conditions, bone marrow MSCs from female 3‐ and 6‐month‐old mice expressed similar levels of bone‐related genes, but significantly greater levels of adipocyte‐related genes, than male MSCs. Female MSCs also responded to rosiglitazone‐induced suppression of osteogenesis at a 5‐fold lower (10 nM) concentration than male MSCs. Female MSCs grown in estrogen‐stripped medium showed similar responses to rosiglitazone as MSCs grown in serum containing estrogen. MSCs from female mice that had undergone ovariectomy before sexual maturity also were sensitive to rosiglitazone‐induced effects on osteogenesis. These results suggest that female MSCs are more sensitive to modulation of differentiation by PPARγ and that these differences are intrinsic to the sex of the animal from which the MSCs came. These results also may explain the sensitivity of women to the deleterious effects of rosiglitazone on bone. J. Cell. Physiol. 230: 296–307, 2015. © 2014 Wiley Periodicals, Inc.